Discovery of knowledge and perception among the indigenous people related to teenage pregnancy and sexual education - Rusli NIF,; Hazidan ANZ,; Abdul Razak RNH,; Abd. Jalil MA,; Muhammad Lokman Md Isa, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examined the knowledge and perceptions of sexual education and teenage pregnancy among Indigenous people in Pekan, Malaysia. The research aimed to address the high rates of teenage pregnancy, particularly among unmarried teenagers, in the country. Through qualitative methods, including semistructured interviews with Indigenous participants, several themes emerged. These themes included the sources of sexual education, such as formal and informal channels, first sexual experiences, safe-sex beliefs, and the importance of sexual education for children. The study also explored perceptions of teenage pregnancy, identifying factors like young marriage and premarital dating. Participants shared their views on premarital motherhood among those under 20 years old, as well as the acceptance and responses of parents and the responsibility of the baby’s father. The study highlighted the complications of teenage pregnancy for both the baby and mother. The findings revealed a lack of sexual education knowledge among Indigenous participants, attributed to limited access to facilities like mobile phones and limited interaction with outsiders. The study recommends further research and the dissemination of awareness and knowledge about sexual education, particularly through campaigns and outreach efforts to Indigenous communities, while also emphasise the need to review the effectiveness of these initiatives.